Mouse models of nonalcoholic steatohepatitis in preclinical drug development. Issue 11 (November 2017) - Hansen, Henrik H.; Feigh, Michael; Veidal, Sanne S.; Rigbolt, Kristoffer T.; Vrang, Niels; Fosgerau, Keld
Highlights: Non-alcoholic steatohepatitis (NASH) is a medical disease of unmet therapeutic need. Numerous drugs are in various stages of clinical development for NASH. Improvement of liver fibrosis is the most important treatment outcome variable. Mouse models of NASH have varying clinical translatability. Anti-NASH drug efficacy can be assessed in relevant mouse models of NASH. Abstract : Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of chronic liver disease in the Western world. NAFLD is a complex spectrum of liver diseases ranging from benign hepatic steatosis to its more aggressive necroinflammatory manifestation, nonalcoholic steatohepatitis (NASH). NASH pathogenesis is multifactorial and risk factors are almost identical to those of the metabolic syndrome. This has prompted substantial efforts to identify novel drug therapies for correcting underlying metabolic deficits, and to prevent or alleviate hepatic fibrosis in NASH. Available mouse models of NASH address different aspects of the disease, have varying clinical translatability, and, therefore, also show different utility in drug discovery.